Analisis Kualitas Permukiman Berbantuan Google Earth di Desa Sungai Kedukan, Kabupaten Banyuasin, Sumatra Selatan - Ruzaina, Urwa; Eni Heldayani; Mirna Taufik (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
The river basin settlement in Sungai Kedukan Village is a settlement located along the river and has an area of approximately 300,000 m2 with RT boundaries covering 8 RTs along the Nibung River, Sungai Kedukan Village with a background of the problem of residential building density where the condition of the buildings is very close together because of the large number of residents living in the settlement, irregular building layout, and lack of facilities and infrastructure. The purpose of the study was to determine the quality of settlements assisted by Google Earth in Sungai Kedukan Village, (DAS), Rambutan District, Banyuasin, South Sumatra. This study uses a quantitative approach with a survey method that has a population and sample using purposive sampling with data processing using the Google Earth application and to conduct analysis, namely by entering formulas from building density parameters, building layout, road width, and access road conditions, as well as by collecting questionnaires to determine the quality of the residential environment. This study shows that the quality of settlements and residential environments in river basin areas produces the same results and is included in various categories, namely poor and moderate.